PENGARUH PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT.PELABUHAN INDONESIA I (PERSERO) MEDAN - Faustyna Faustyna; Jumani Jumani (JURNAL ILMIAH MANAJEMEN & BISNIS, 2015)
The analysis technique used in this research is the analysis of quantitative data, ie, test and analyze the data by calculating the numbers and then draw conclusions from these tests with test equipment product moment correlation and multiple correlation, but in practice the data processing in the study was not as if it manually , but using SPSS statistical software. There was a significant influence on the performance of the employee's career development in Indonesia PT.Pelabuhan I (Persero) Medan.Ada significant influence on the performance of the labor discipline I PT.Pelabuhan Indonesia (Persero) Medan.Ada significant influence career development and work discipline on the performance of employees at PT I .Pelabuhan Indonesia (Persero) Medan.  Keywords: Career development, Discipline of work, performance